2000
DOI: 10.1034/j.1600-0528.2002.017416.x
|View full text |Cite
|
Sign up to set email alerts
|

Innate and adaptive lymphoid cells in the human liver

Abstract: Because of its location and function, the liver is continuously exposed to a large antigenic load that includes pathogens, toxins, tumor cells and harmless dietary antigens. The range of local immune mechanisms required to cope with this diverse immunological challenge is now being appreciated. The liver has an "epithelial constitution" and contains large numbers of phagocytic cells, antigen-presenting cells and lymphocytes and is a site for the production of cytokines, complement components and acute phase pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
316
0
8

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 373 publications
(344 citation statements)
references
References 80 publications
(179 reference statements)
20
316
0
8
Order By: Relevance
“…Intrahepatic gd T cells may also have a role in repair and regeneration in the liver through secretion of growth factors. 6 In addition to conventional lymphocytes, normal human livers were populated with T cells expressing the NK receptor CD56 (CD3 þ CD56 þ ) with a proportion of them also expressing CD161…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intrahepatic gd T cells may also have a role in repair and regeneration in the liver through secretion of growth factors. 6 In addition to conventional lymphocytes, normal human livers were populated with T cells expressing the NK receptor CD56 (CD3 þ CD56 þ ) with a proportion of them also expressing CD161…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] To avoid pathological consequences, mechanisms that reduce unnecessary activation of the immune system are required in the face of continuous exposure to pathogens, toxins, tumour cells and dietary antigens. 7 The liver has a complex histological structure, which consists primarily of hepatocytes (70% of hepatic cellular component), with intrahepatic lymphocytes (IHL) constituting 16-22% of the remaining nonparenchymal cells (30%).…”
mentioning
confidence: 99%
“…18 The liver also plays a key role in the innate immune response by influencing the homing and differentiation of NK cells. [31][32][33][34] Up to 65% of all lymphocytes present in the normal liver consists of NK cells, NKT cells, and cd T cells, and the frequency of NK cells among human intrahepatic lymphocytes ranges between 25% and 30%. 31,32 Furthermore, NK cells are located in the liver sinusoids, adherent to the liver sinusoidal endothelial cells and, thus, are well situated to eliminate arriving metastasizing tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for studying these lymphocytes is that they are believed to play important roles in the innate immune response to viral infections by production of IFN-␥ and/or the recognition of virally-infected cells. 8 These functions are an important aspect of the immediate response of the host to the virus and are believed to control the initial infection. Accordingly, injection drug users who remain human immunodeficiency virus-1 uninfected despite many years of high-risk exposure demonstrate significantly augmented NK cell lytic activities and cytokine secretion when compared to human immunodeficiency virus-1 infected injection drug users.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although a number of groups have demonstrated that the presence of HCV-specific effector responses correlate with attenuated histologic severity, 6,7 considerable gaps exist in our understanding of how the immune response shapes HCV recurrence post-OLT. In particular, the role of innate immunity, as represented by natural killer (NK) and natural T (NT) cells, 8 the same cell populations that are usually associated with the very early stages of an acute immune response, has not been examined. We hypothesized that the nature of the innate immune response prior to OLT would correlate with the severity of HCV recurrence following LT.…”
Section: See Editorial On Pagementioning
confidence: 99%